FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN PRODUK KERUPUK KULIT DI KOTA PEKANBARU - A. Eko, Prasetio; Azwar, Harahap; Yusni, Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Skin crackers are one of the processed food industries that are quite popular in the community. Apart from cultural factors, the majority of the population likes skin crackers, another factor is the existence of cowhide waste in the Slaughterhouse which is the main ingredient for abundant skin crackers and facilitates the production of crackers. leather in Pekanbaru City. In analyzing the number of requests for skin crackers in Pekanbaru City, there are many factors that influence the demand. In this study, there are 3 factors that become independent variables in the analysis of the demand for skin crackers in Pekanbaru City, including income (X1), taste (X2), and the price of skin crackers (X3). Meanwhile, the dependent variable is demand (Y). The method used is multiple linear regression analysis, namely the partial regression test (t test), simultaneous coefficient test (F test) and the coefficient of determination (R2). The results of this study are based on statistical testing of the partial regression equation, namely the independent variable income (X1), taste (X2) and price (X3) have a significant effect on the dependent variable, namely the demand for skin crackers in Pekanbaru City. Based on the regression equation simultaneously, it shows that income, taste and price have a significant effect on the demand for skin crackers. Meanwhile, based on the coefficient of determination (R2) shows that the independent variable has an effect of 71.1% on the demand for skin crackers, the remaining 28.9% is influenced by other variables not included in this regression model.Keywords: Demand, Income, Taste, Price